A Review: Carissa Congesta: Phytochemical Constituents, Traditional Use and Pharmacological properties - Devmurari, V.; P, Shivanand; Goyani, M.B.; Vaghani, S.; Jivani, N.P. (Pharmacognosy Reviews)
Various herbal drugs individually or in combination have been recommended for the treatment of different disease. The C.congesta commonly known as “karanda” has been recognized in different system of traditional medicine to cure various diseases. It contains several phytochemical constituents belonging to terpenoids category. The root is attributed with bitter, stomachic; antidiarrhoel, vermifuge and antianthelmintic properties. The unripe fruit is used medicinally as an astringent. The ripe fruit is taken as an antiscorbutic and remedy for biliousness. The leaf decoction is valued in cases of intermittent fever, diarrhoea, oral inflammation and earache. Additionally C.congesta has shown wide range of evidences for its cardiotonic, hepatoprotective, free radical scavenging and xanthine oxidase inhibitory, histamine releasing, antirhumatic, antibacterial, antiviral and anticonvulsant activity. A higher gross heat value of this species indicates its higher potential to be used as good fuel source.
Keywords: Karanda; Phytochemical constituents; Traditional uses; and Pharmacological properties